One weighs a pound, and the other pounds away!
Answer:
6
Step-by-step explanation:
1+1+1+1+1+1 = 6
Answer:
1. L1 = ![\frac{L2}{X(O2 -O1)}](https://tex.z-dn.net/?f=%5Cfrac%7BL2%7D%7BX%28O2%20-O1%29%7D)
2. O2 = ![\frac{L2 - L1(1 + XO1)}{XL1}](https://tex.z-dn.net/?f=%5Cfrac%7BL2%20-%20L1%281%20%2B%20XO1%29%7D%7BXL1%7D)
Step-by-step explanation:
Given: x = ![\frac{L2 - L1}{L1(O2 -O1)}](https://tex.z-dn.net/?f=%5Cfrac%7BL2%20-%20L1%7D%7BL1%28O2%20-O1%29%7D)
1. To make L1 the subject of formula;
x = ![\frac{L2 - L1}{L1(O2 -O1)}](https://tex.z-dn.net/?f=%5Cfrac%7BL2%20-%20L1%7D%7BL1%28O2%20-O1%29%7D)
cross multiply to have;
L2 - L1 = xL1(O2 - O1)
collect like terms,
L2 = xL1(O2 - O1) + L1
factorize the right hand side;
L2 = L1[x(O2 - O1)]
L1 = ![\frac{L2}{X(O2 -O1)}](https://tex.z-dn.net/?f=%5Cfrac%7BL2%7D%7BX%28O2%20-O1%29%7D)
2. To make O2 the subject of formula;
x = ![\frac{L2 - L1}{L1(O2 -O1)}](https://tex.z-dn.net/?f=%5Cfrac%7BL2%20-%20L1%7D%7BL1%28O2%20-O1%29%7D)
cross multiply to have;
L2 - L1 = xL1(O2 - O1)
open the bracket to have;
L2 - L1 = xL1O2 - xL1O1
⇒ xL1O2 = L2 - L1 + xL1O1
O2 = ![\frac{L2-L1 + XL1O1}{XL1}](https://tex.z-dn.net/?f=%5Cfrac%7BL2-L1%20%2B%20XL1O1%7D%7BXL1%7D)
= ![\frac{L2 - L1(1 + XO1)}{XL1}](https://tex.z-dn.net/?f=%5Cfrac%7BL2%20-%20L1%281%20%2B%20XO1%29%7D%7BXL1%7D)
Answer:
6^8=6*6*6*6*6*6*6*6
=1679616
Step-by-step explanation:
In this expression the exponent shows that how many times 6 will be multiplied.
6^8=6*6*6*6*6*6*6*6
=1679616